The pros and cons of listening devices. (25th September 2017) - DALE, ROBERT
Abstract: Vastly improved speech recognition, backed by a more slowly improving ability to make sense of the recognized speech, has brought state-of-the-art NLP into our homes in the form of smart speakers and other devices that listen. There's no doubt these devices can be incredibly useful, but they also may also support incursions into our privacy. We look at where we are today, consider what might be coming, and express just a tad of caution.